All-Ukrainian interdisciplinary scientific and practical conference with international participation "Patologies of the temporomandibular joint: diagnosis, treatment protocols" - Primak, С. Л. (Actual Dentistry, 2024)
All-Ukrainian interdisciplinary scientific and practical conference with international participation "Patologies of the temporomandibular joint: diagnosis, treatment protocols"